Anonimitas Ruang Siber dan Pengalaman Remaja dalam Melakukan Perundungan di Media Sosial - Pradipta, Ade Devia (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 2 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONAL, 2023)
A survey conducted by Polling Indonesia in collaboration with the Indonesian Internet Service Providers Association (APJII) found that around 49% of netizens had been the target of bullying on social media. Both traditional bullying and that occurred in cyberspace, arose as a result of imbalance of power between the perpetrator and the victim. The Uses and Gratification theory is used to see what reasons or motivations bullies have for carrying out bullying in cyberspace. Data was collected using a survey method with an instrument in the form of a questionnaire. The data was then analyzed descriptively by looking at the average of each question item. The underlying motivation for perpetrators to bully on social media is anonymity, it is a fun thing to do, it relieves boredom, jealousy, and it is also a form of self-defense from unpleasant acts they experience on social media. From the victim experiences of bullying on social media is being harassed by hurtful sentences in the form of hate speech, ridicule/insults, and sentences that make them uncomfortable. On the other hand, what bullies most often do is upload other parties' chats without the owner's permission